Sesquiterpenes From Oplopanax elatus Stems and Their Anti-Photoaging Effects by Down-Regulating Matrix Metalloproteinase-1 Expression via Anti-Inflammation - Yan, Jiejing; Hao, Mimi; Han, Yu; Ruan, Jingya; Zheng, Dandan; Sun, Fan; Cao, Huina; Hao, Jia; Zhang, Yi; Wang, Tao (Frontiers in Chemistry, 2021)
In the process of continuing to investigate ultraviolet b (UVB) irradiation protective constituents from Oplopanax elatus stems, nine new sesquiterpenes, named as eurylosesquiterpenosides A–D (1–4), eurylosesquiterpenols E–I (5–9), and ten known ones (10–19) were gained. Their structures were established by analysis of their NMR spectroscopic data, and electronic circular dichroism calculations were applied to define their absolute configurations. In addition, ultraviolet B (UVB) induced HaCaT cells were used to study their anti-photoaging activities and mechanism. The results consolidated that compounds 7, 11, and 14 could improve the survival rate of HaCaT cells in concentration dependent manner at 10, 25, and 50 μM. Furthermore, western blot assay suggested that all of them could inhibit the expression of matrix metalloproteinase-1 (MMP-1), and increase the level of type I collagen markedly. Compounds 11 and 14 could reduce the phosphorylation of extracellular signal-regulated kinase and p38, respectively. Besides, compounds 7, 11, and 14 could significantly down-regulate the expression of inflammation related protein, such as tumor necrosis factor-α and cyclooxygenase-2, which indicated that they played anti-photoaging activities by reducing MMP-1 expression via down-regulating the production of inflammatory mediators and cytokines in UVB-induced HaCaT cells.